The development of intercarrier interference mitigation technique in OFDM system - Ali, Ismail Mohamed (Kulliyyah of Engineering, International Islamic Universiti Malaysia, 2017)
Orthogonal Frequency Division Multiplexing (OFDM) is a popular multiplexing scheme of modulation for the high rate of data transmission in the modern world. However, there is a problem with the system because of its instability to frequency offset existed between the received and the transmitted signal caused by Doppler shift at the receiver and transmitter oscillator frequencies. Multipath channel leads to loss of frequency of subcarriers inter carrier interference, which are not dependent each other, resulting to inter carrier interference (ICI). In this dissertation, all the effect of inter carrier interference has been the discussion to mitigate ICI. The existing methods proposed by researchers have distorted the orthogonally. The dissertation examines the effectiveness of mitigation Kalman Filter in reference to the advantages derived from literature. Our proposed Kalman filter can be significantly by ICI, it is shown one of the way technique is effective in mitigating the effects in the ICI, like the Kalman filter in this frequency offset introduces inter-carrier interference (ICI) in the OFDM systems. In the literature review, it shows different ways to mitigate ICI.in this dissertation using Kalman filter in OFDM systems using the type of modulation which is QAM-2.Bit error rate (BER) performance is measured between transmitter and receiver. Inter carrier interference can be mitigated by Kalman filter to correction of sub-carrier spacing accordingly.QAM-2 modulation is considered as part of kalman filter system to mitigation ICI. Inter carrier interference is weakness performance of OFDM transmit. A signal transmit a lot of noise and signal interference multipath to receiver. To solve problem using kalman filter with modulation QAM-2 in the dissertation. In this dissertation to develop mitigation technique to reduce inter carrier interference using coding matlab for kalman filter combine QAM-2.